Determining the stress levels and burnout among undergraduate medical students - Peter Olanrewaju Ibikunle; Gospel N. Umeakubuilo; Timothy Chukwuka Igbokwe (Advances in Biomedical and Health Sciences)
Background: In addition to coping with the normal stressors of everyday life, medical students must deal with stressors specific to their field of study, which may result in reduced productivity and burnout if left unchecked. This study aimed to determine the levels of perceived stress, stressors, and burnout among medical students at the College of Health Sciences. Methods: This cross-sectional survey included 361 consenting students recruited from the faculties of Medicine, Basic Medical Sciences, and Health Sciences at the College of Health Sciences in Nigeria. The Perceived Stress Scale, Student Stress Inventory, and Maslach Burnout Inventory were used as the research instruments. Data were analyzed using frequency counts, percentages, ranges, means, and standard deviations. The stated hypotheses were tested using the Mann–Whitney U test, Kruskal–Wallis test, and Spearman rank order correlation test. The level of significance was set at P < 0.05. Results: Moderate degree of perceived stress (21.54) and burnout (emotional exhaustion = 20.93, depersonalization = 5.65, and personal achievements = 29.31) while academics (22.9 ± 6.04) and the environment (24.02 ± 6.51) were significant stressors. A significant correlation was found between perceived stress and burnout components (P = 0.001). Conclusion: This study showed a moderate level of perceived stress and burnout among the medical students at the college which might be attributed to the increasing academic workload and unfavorable environmental conditions identified as significant stressors.